2018
DOI: 10.1038/s41598-018-33974-y
|View full text |Cite
|
Sign up to set email alerts
|

Nonstationary Temperature-Duration-Frequency curves

Abstract: Persistent extreme heat events are of growing concern in a climate change context. An increase in the intensity, frequency and duration of heat waves is observed in several regions. Temperature extremes are also influenced by global-scale modes of climate variability. Temperature-Duration-Frequency (TDF) curves, which relate the intensity of heat events of different durations to their frequencies, can be useful tools for the analysis of heat extremes. To account for climate external forcings, we develop a nons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 37 publications
(43 reference statements)
2
39
0
Order By: Relevance
“…While the analysis so far has focused on individual heatwave metric trends, studies indicate that a multivariate approach considering all metrics in a more comprehensive manner may better represent the full impact of heatwave events (Mazdiyasni et al, 2019; Ouarda & Charron, 2018). Quantifying the likelihood of heatwave events occurring with different intensities and durations can have practical applications.…”
Section: Resultsmentioning
confidence: 99%
“…While the analysis so far has focused on individual heatwave metric trends, studies indicate that a multivariate approach considering all metrics in a more comprehensive manner may better represent the full impact of heatwave events (Mazdiyasni et al, 2019; Ouarda & Charron, 2018). Quantifying the likelihood of heatwave events occurring with different intensities and durations can have practical applications.…”
Section: Resultsmentioning
confidence: 99%
“…Current metrics evaluate individual heat wave characteristics, such as the hottest day of each year or longest duration of consecutive hot days 7,17,22,29,31,33 . However, current univariate indicators often underestimate the impacts of heat waves because they fail to characterize the extreme event in a comprehensive manner 23,34,35 . The impacts of individual heat wave characteristics can be amplified when considered concurrently (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, according to climate projections and due to climate change, the probability of heat waves occurring early or late in the season should increase [17,18]). Ouarda and Charron [19] studied over 50 years of heat waves in six stations distributed across the Province of Québec and found a non-negligible trend of the intensity, magnitude, and duration of these events. Another study reported that the number of heat-wave days could increase by up to 13 days in the period 2021 to 2050 and even by up to 40 days in the period 2071 to 2100 in the Iberian Peninsula and the Mediterranean region [20].…”
Section: Introductionmentioning
confidence: 99%